Analysis of Flavonoids from Eugenia uniflora Leaves and Its Protective Effect against Murine Sepsis. (20th December 2012) - Rattmann, Yanna D.; de Souza, Lauro Mera; Malquevicz-Paiva, Simone M.; Dartora, Nessana; Sassaki, Guilherme Lanzi; Gorin, Philip A. J.; Iacomini, Marcello
Abstract : Eugenia uniflora, referred to as Pitanga cherry shrub, is largely distributed in tropical and subtropical America. This plant is cultivated in many countries and it is suitable for the production of juice, frozen pulp, and tea. Besides, it can be used as treatment for inflammatory diseases. We reported that a flavonoid-rich fraction (HE-Bu) obtained from leaves decreased the lethality induced by cecal ligation and puncture (CLP), a clinically relevant model of sepsis. The oral administration of HE-Bu reduced the late mortality rate by 30%, prevented neutrophil accumulation in lungs, decreased TNF- α and IL-1 β serum levels, and markedly decreased iNOS and COX-2 protein expression by ileum cells. Chemical investigation showed myricetin and quercetin rhamnosides as the major components of this fraction. The results showed that HE-Bu protected mice from sepsis and indicated that this edible plant produces compounds that could be considered as potential adjuvants for sepsis treatment.